Immune mechanisms of sublingual immunotherapy and mycobacterial adjuvants in the treatment of allergic disease - (:unkn) unknown (Bentham Science Publishers B.V., 2006)
While safety and efficacy of specific immunotherapy (SIT) by the sublingual route in patients with allergic asthma/rhinitis have now been largely documented, the immunological mechanisms have only started to be investigated. Most likely, the allergen captured within the oral mucosa by Langerhans-like dendritic cells (DCs), subsequently mature and migrate to proximal draining lymph nodes, which then induce T lymphocytes with regulatory function. Animal experiments point to enhanced expansion of TGF-β, IL-10 and Fox p3 mRNA in CD4+ T cells, indicators of tolerance, induced by mucosal vaccination. Meanwhile, although there is still no firm proof in human, data on increase in allergen-induced IL-10 and allergen-specific IgA secretion supports the possible role of T regulatory cells in sublingual immunotherapy. Furthermore, detection of high amounts of lipopolysacharide receptor CD14 on oral DCs support the idea of using adjuvants such as mycobacteria along with allergen within the oral cavity, which may further potentiate the immuno-modulatory effect. Adjuvants that induce the generation of allergen-specific T regulatory cells have been suggested to increase the success of SIT. Supporting this concept, Mycobacterium vaccae was demonstrated to induce CD4+CD45RBlow T regs that secrete IL-10 and TGF-β. © 2006 Bentham Science Publishers Ltd.
Keywords: Adjuvant; Allergen-specific immunotherapy; Allergy; Mycobacteria; Oral dendritic cells; Sublingual immunotherapy